Nursery Culture Performance of Litopenaeus vannamei with Probiotics Addition and Different C/N Ratio Under Laboratory Condition - . WIDANARNI; DEBY YUNIASARI; . SUKENDA; JULIE EKASARI (Bogor Agricultural University, Indonesia, 2010)
Application of bioflocs technology and probiotics has improved water quality and production of Pacific white shrimp (Litopenaeus vannamei) culture. This experiment was to verify the effect of probiotic bacteria addition and different carbon:nitrogen (C:N) ratio on water quality and performance of Pacific white shrimp nursery culture. Nursery culture was carried out for 25 days in an aquarium under laboratory condition with stock density of one Post-Larvae (PL) (poslarval) per liter (24 PL/aquarium) of PL16 shrimp. Different C:N ratio resulted a significant difference on shrimp production performance. Treatment of 10 C:N ratio demonstrated the best shrimp growth (20.37 + 0.48% per day in weight and 6.05 + 0.41% per day in length), harvesting yield (1180 + 62 g/m3) and feed efficiency (121 + 6%). There was however no significant difference observed between treatments in water quality.